An introduction to signal and system analysis - Helstrom, Carl W. (San Francisco, California : Holden-Day, Inc., 1978)
This book was written for a one-quarter course that serves as a bridge between our sophomore sequence on linear networks and the study of random processes in communications and electronics.
I. Fourier series -- II. The fourier transform -- III. State variables -- IV. Stability and feedback control system -- V. Z-Transform.
Includes bibliographical references and index.
Keywords: ENGINEERING -- MATHEMATICS